Helmet Deduction Using Image Processing - A Mohamed Syed Ali (Institute of Advanced Engineering and Science, 2018)
The project aim is to build a smart, little power bicycle dashboard with advanced vision sensor to find whether the rider is wearing a helmet or not and allows start/stop the bike ignition system. Even while riding the bicycle, the system continues the monitoring process, prevents the fire and sends alert messages to traffic authorities if the helmet not worn at any point in time. An alcohol sensor is built-in within the dashboard to prevent the drunk driving situation. GPS and motion sensors assist the system identifies accident scenario and sends alert SMS to traffic authorities and family members. Twitter’s Sentiment Analysis on Gsm Services using Multinomial Naïve Bayes discussed in [11]. The dashboard unit has a Bluetooth transceiver that helps the system to communicate with an Android mobile app running on the user Smartphone to provide SMS sending capability. Weighted Least Squared Approach to Fault Detection and Isolation for GPS Integrity Monitoring discussed in [10]. This design eliminates building power-hungry GSM modems into the vehicle dashboard thus saving vehicle battery power. Model for Post placement Mousing based on GSM in Long-Distance discussed in [9].